A literacy tutoring experience for prospective special educators and struggling second graders. - Spear-Swerling, Louise (Journal of Learning Disabilities, 2009)
This study examined the learning of teacher candidates taking a language arts course in a special-educator preparation program and that of the second graders they tutored in a supervised field component of the course. Teacher candidates' knowledge of literacy instruction was assessed using five knowledge tasks; children were assessed on several measures of basic reading and spelling skills as well as on their knowledge of phonics concepts such as syllable types. Teacher candidates generally had inaccurate perceptions of their knowledge at pretest, but their knowledge improved significantly on all tasks after course instruction. Tutored children improved significantly from pre- to posttest on all assessments. The study suggests that carefully designed literacy coursework with field experiences can benefit both prospective special educators and struggling readers.
Keywords: *Education, Professional/st [Standards]; *Education, Special/st [Standards]; *Educational Status; *Professional Competence/st [Standards]; *Reading; *Remedial Teaching/st [Standards]; Adolescent; Adult; Child; Culture; Curriculum; Curriculum/st [Standards]; Education, Professional; Education, Special; Educational Status; Female; Humans; Linguistics; Linguistics/ed [Education]; Male; Middle Aged; Phonetics; Professional Competence; Questionnaires; Reading; Remedial Teaching; Self Concept; Special education; Surveys and Questionnaires; Teacher education; Teacher knowledge; Teacher perceptions; Young Adult; adolescent; adult; article; child; cultural anthropology; curriculum; dept.sed; education; educational status; female; human; linguistics; male; middle aged; phonetics; professional competence; questionnaire; reading; self concept; standard; teaching; vocational education